THE RATE OF CURRENT CHANGE DURING A SHORT CIRCUIT IN THE POWER CIRCUITS OF THE ELECTRIC ROLLING STOCK WITH REGARD TO EDDY CURRENTS - Dubinets, L. V.; Karzova, O. O.; Bondarenko, Yu. S. (Science and Transport Progress, 2010)
In the article the issue of influence of vortical currents on rate of change of short circuit current is considered, a mathematical model for the calculation of short circuit currents in the traction mode in the power circuits of DC electric rolling stock is presented, and the research results are given.